Oral health behavior patterns among Tanzanian university students: a repeat cross-sectional survey - Åstrøm Anne; Masalu Joyce (BMC, 2001)
Abstract Purpose This study examines oral health behavioral trends and the development of sociodemographic differences in oral health behaviors among Tanzanian students between 1999 and 2000. Methods The population targeted was students attending the Muhimbili University College of Health Sciences (MUCHS) at the University of Dar es Salaam (UDSM), Dar es Salaam, Tanzania. Cross-sectional surveys were conducted and a total of 635 and 981 students, respectively, completed questionnaires in 1999 and 2001. Results Cross-tabulation analyses revealed that in 1999, the rates of abstinence from tobacco use, and of soft drink consumption, regular dental checkups, and intake of chocolate/candy were 84%, 51%, 48%, and 12%, respectively, among students of urban origin and 83%, 29%, 37%, and 5% among their rural counterparts. The corresponding rates in 2001 were 87%, 56%, 50%, and 9% among urban students and 84%, 44%, 38%, and 4% among rural ones. Multiple logistic regression analyses controlling for sex, age, place of origin, educational level, year of survey, and their interaction terms revealed a significant increase in the rate of soft drink consumption, implementation of oral hygiene measures, and abstinence from tobacco use between 1999 and 2001. Social inequalities observed in 1999, with urban students being more likely than their rural counterparts to take soft drinks and go for regular dental checkups, had leveled off by 2001. Conclusion This study provides initial evidence of oral health behavioral trends, that may be utilized in the planning of preventive programs among university students in Tanzania.